2018
DOI: 10.1039/c7nj03113k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of appended hydroxyl groups and ligand chain length on copper coordination and oxidation activity

Abstract: The effects of appended hydroxyl groups and the chain length of a series of (imino)pyridine ligands on copper coordination and copper-catalyzed aerobic oxidation of alcohols were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…At the same time as the ionic radius of Cu (0.73 Å [ 12 ] ) is smaller than that of In, Cu can also occupy vacant sites of In (0.94 Å [ 13 ] ) at the ultrathin surface. In addition, the bond lengths of In—In, Se—Se, Cu—Cu, In—Se, Cu—Se, Cu—O, and In—O are 2.82, [ 14 ] 2.37, [ 15 ] 3.64, [ 16 ] 2.68, [ 17 ] 2.46, [ 18 ] 1.85, [ 19 ] and 2.16 Å, [ 20 ] respectively. When comparing bond lengths for In—Se and In—O one finds that the bond length for In—Se is larger than the bond length of In—O.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time as the ionic radius of Cu (0.73 Å [ 12 ] ) is smaller than that of In, Cu can also occupy vacant sites of In (0.94 Å [ 13 ] ) at the ultrathin surface. In addition, the bond lengths of In—In, Se—Se, Cu—Cu, In—Se, Cu—Se, Cu—O, and In—O are 2.82, [ 14 ] 2.37, [ 15 ] 3.64, [ 16 ] 2.68, [ 17 ] 2.46, [ 18 ] 1.85, [ 19 ] and 2.16 Å, [ 20 ] respectively. When comparing bond lengths for In—Se and In—O one finds that the bond length for In—Se is larger than the bond length of In—O.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that transition metal complexes play a crucial role in oxidation process. Many transition metal catalysts including ruthenium (Shapley et al, 2000; Lybaert et al, 2017; Sarbajna et al, 2017; Moore et al, 2019), palladium (Stahl, 2004; Sigman and Jensen, 2006; Ho et al, 2018), copper (Velusamy et al, 2006; Jehdaramarn et al, 2018; Lagerspets et al, 2019), and iron (Coleman et al, 2010; Stanje et al, 2018) have been reported for promoting the oxidation of alcohols. Among them, ruthenium compounds are intensively studied because of their rich structures and various valence states.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These complexes showed various coordination modes up to the tetradentate. [4][5][6] Their structural stability and catalytic efficiency made them useful mainly in the area of structural studies, [7] photoluminescence, [8][9][10] spectroscopy, [11] transfer hydrogenation reactions, [12] biological applications, [13] oxidation catalyst, [14] catalysts for alkene polymerization, [15] epoxidation, [16] olefin [17,18] and MMA polymerizations. [19] Poly (methylmethacrylate) (PMMA), an acrylic polymer, is commonly used as a thermoplastic with enhanced optical properties and wide range of industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes showed various coordination modes up to the tetradentate . Their structural stability and catalytic efficiency made them useful mainly in the area of structural studies, photoluminescence, spectroscopy, transfer hydrogenation reactions, biological applications, oxidation catalyst, catalysts for alkene polymerization, epoxidation, olefin and MMA polymerizations…”
Section: Introductionmentioning
confidence: 99%